Green Public Procurement as a Tool for the Transition from the Linear Model of Economy to the Circular Economy - Karnavos, Dimitrios; Mitoula, Roido; Tragaki, Alexandra; Apostolopoulos, Constantinos (Advances in Social Sciences Research Journal, 2022)
The present paper first investigates the penetration of Green Public Procurement in the Greek reality and then how Green Public Procurement functions as a tool for the transition from the linear to a circular economy model. To serve this purpose, a questionnaire was structured with a total of 38 questions. The Municipalities formed by the “Kallikratis” programme, were selected as a sample, which enter into contracts with Green Public Procurement for a wide range of goods and services. The majority of the questions gave the possibility to choose from the specific number of specific answers at a time, while some of them required the writing of an answer by the respondent himself. For the drafting of the questions, the most important elements related to the subject of Green Public Procurement were taken into account. As far as their structure is concerned, it was the result of the overall research carried out in the Greek and foreign annotated bibliography, while data were also drawn from questions of a similar nature that were altered from time to time in the field of Green Public Procurement. A very brief introduction to the conceptual approach to Green Public Procurement was also included in the structure of the questionnaire. Therefore, the respondent had the opportunity, in a very short period of time, to understand the subject of the investigation and to answer the questions that followed or to send the questionnaire to the relevant Municipal Department.